Lactobacillus plantarum Fermentation Effect on Tannin Reduction, Proximate Analysis, and Protein Profiles of Ganyong (Canna edulis Kerr) Flour - Azor Yulianus Tefa; Arie Srihardyastutie; Sasangka Prasetyawan (Chemistry Department, The University of Brawijaya, 2019)
One of the problems in using ganyong (Canna edulis Kerr)as food is the presence of tannin, an antinutritional substance, that can reduce the nutritional quality of ganyong. The purpose of this study was aimed to analyze the effect of fermenting ganyong using Lactobacillus Plantarumbacteria on the chemical compounds and the reduction of tannin level in its flour. Theresults showed that the optimum conditions of fermenting ganyong were at pH 6, the temperature of 40 oC, and at the fermentation time of 36 hours. At the optimum conditions, Lactobacillus Plantarumwas able to decrease tannin content in ganyong from 2.53 mg/mL to 0.84 mg/mL. The reduction of tannin content is due to the activity of tannase produced by the microorganisms. Fermentation caused the enrichment protein content, from 1.87% to 2.01% and the reduction of starch, amylose, and amylopectin contents to 51%, 16.82%, and 38.08% from 60.19%, 18.27%, and 43.49% respectively. SDS-PAGE results showed that the protein profiles changed in ganyong sample after the fermentation process. Protein with a molecular weight of 72.49 kDa which showed in the non-fermented ganyong, did not appear in the fermented ganyong, and protein band intensities also showed changes.